Developing an Ecoprint-Based Instructional Guide to Enhance Entrepreneurial Skills in Deaf Students: A Study in Indonesian Special Schools - Intan Andriyana Ginting; Sukinah Sukinah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Entrepreneurship education for deaf learners remains limited due to the scarcity of instructional materials that match their visual learning needs and inclusive pedagogical requirements. Existing resources in Indonesian Special Schools (SLBs) are often generic, text-heavy, and insufficient for supporting hands-on vocational learning. This study aims to address this gap by developing and validating an ecoprint-based instructional guide designed to strengthen entrepreneurial competencies among deaf students. Using a modified Borg and Gall Research and Development model, four stages were implemented: needs analysis, instructional design, prototype development, and expert validation. The resulting guide integrates ecoprint techniques with visually rich, sign-language-supported instructional strategies. Content validation by special education and entrepreneurship experts yielded scores above 90%, while media validation confirmed strong accessibility and visual clarity. Trial implementation indicated notable improvements in students’ engagement, independence, creativity, and understanding of entrepreneurial processes. The guide also enhanced teachers’ ability to deliver structured, culturally grounded, and sustainable entrepreneurship instruction. This study demonstrates that ecoprint is an effective medium for experiential, inclusive, and environmentally oriented entrepreneurial learning. Future research should explore the guide’s long-term impact, its adaptation for students with other disabilities, and its potential integration with digital and community-based entrepreneurship models.